Non-invasive assessment of placental perfusion in vivo using arterial spin labeling (ASL) MRI: A preclinical study in rats. (February 2019) - Deloison, Benjamin; Salomon, Laurent J.; Quibel, Thibaud; Chalouhi, Gihad E.; Alison, Marianne; Balvay, Daniel; Autret, Gwennhael; Cuenod, Charles-André; Clement, Olivier; Siauve, Nathalie
Abstract: Introduction: Non-invasive assessment of placental perfusion is of great interest to characterize placental function in clinical practice. This article proposes a strictly non-invasive MRI technique using ASL to quantify placental blood flow in vivo. The aim of this study was to develop a fMRI tool to quantify placental blood flow (PBF) in rat, by using arterial spin labeling (ASL) MRI at 4.7 T. Materials and methods: MRI was performed with a dedicated magnet for small animals, in pregnant rats on day 20 of the 22-day gestation period. A Look-Locker flow-sensitive alternating inversion recovery gradient echo sequence was developed as ASL technique (TE: 1.55 ms; TR: 3.5 ms, TI: 56 ms, deltaTI: 56 ms, FA: 20°, Matrix: 128 × 128, 8 segments, 4 Nex). Labeling was performed with global and slice-selective inversions, and T1 map was obtained for each mode of inversion. PBF was then derived from a compartmental model of the variation of T1 between global and slice-selective inversions. Results: The full protocol was completed and ASL image post-processing was successful in 18 rats. Forty-seven placentas were analyzed, with a mean PBF of 147 ± 70 ml/min/100 g of placenta, consistent with published values of placental perfusion using invasive techniques. Conclusion: ASL MRI is feasible for the quantification of PBF in rats at 4.7 T. This technique, which requires no administration of contrast media, could have implications for non-invasive longitudinal and in vivo animal studies and may be useful for the management of human pregnancies. Highlights: ASL MRI permits to quantify Placental Blood Flow in rat. ASL gives quantitative assessment of tissular blood flow without any invasiveness. ASL could have implications for the management of high-risk pregnancies.